2021
DOI: 10.3389/frsc.2021.710549
|View full text |Cite
|
Sign up to set email alerts
|

Urban Green Infrastructure for Poverty Alleviation: Evidence Synthesis and Conceptual Considerations

Abstract: The multiple benefits of urban green infrastructure (UGI) that support sustainable cities are increasingly acknowledged, and yet the bulk of research over the past decade or so has focused on only a small subset of the numerous benefits, notably recreation, physical and mental health, and regulating services. In contrast, there is very little information on the contribution of UGI to several of the other Sustainable Development Goals (SDGs), and in particular SDG 1 of reducing poverty, despite the pervasivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 87 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…To date, the analyses of UGI reported by several authors [22][23][24][25][26] revealed that UGIs have multiple benefits, such as recreation, improving physical and mental health, and regulating services. However, less reports have been found on the reduction of unemployment and economic benefits of UGI that serve as a smokeless industry (urban tourism), which has a significant role in poverty alleviation of developing countries, such as Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the analyses of UGI reported by several authors [22][23][24][25][26] revealed that UGIs have multiple benefits, such as recreation, improving physical and mental health, and regulating services. However, less reports have been found on the reduction of unemployment and economic benefits of UGI that serve as a smokeless industry (urban tourism), which has a significant role in poverty alleviation of developing countries, such as Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…However, less reports have been found on the reduction of unemployment and economic benefits of UGI that serve as a smokeless industry (urban tourism), which has a significant role in poverty alleviation of developing countries, such as Ethiopia. In addition, many UGIs lack appropriate planning and urban infrastructure networks, and do not focus on preventing human induced climate changes and lately emerged social health concerns, such as the COVID-19 pandemic [23][24][25][26]. Out of 171 reports on UGI, the vast majority of the research was from the United States, Australia, and the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Provisioning services were the least mentioned, which is at odds with the widespread collection of wild foods, traditional medicines, firewood and flowers for home use or income generation from formal and informal PUGS in South African cities (Garekae and Shackleton, 2020;Sardeshpande and Shackleton, 2023), as well as urban agriculture in public and private spaces (Kanosvamhira, 2023). Such provisioning services are especially important for the urban poor (Shackleton, 2021), although increasingly threatened by urban growth and densification (Lindley et al, 2018). For example, Kaoma and Shackleton (2015) found that, on average, 20% of income (cash and non-cash) amongst low-income urban households (and 30% for the poorest) was from products collected from urban trees and bushes.…”
Section: Discussionmentioning
confidence: 99%
“…This may involve creating universally accessible pathways, incorporating culturally relevant design elements, and implementing policies that prioritize access for marginalized groups. Inclusive access to UGI benefits ensures that the positive social impacts, such as improved health and community engagement, are experienced by the entire urban population (Shackleton, 2021).…”
Section: Social Impacts Of Urban Green Infrastructure (Ugi)mentioning
confidence: 99%